Frequency modulated circular dichroism spectroscopy: application to ICN photolysis - Hancock, G; Richmond, G; Ritchie, G; Taylor, S; Costen, M; Hall, G (2010)
CN photofragments produced in the 248 nm photolysis of ICN are characterised by frequency-modulated absorption spectroscopy in the red A 2Π ← X2Σ+ system. A range of high rotational states in both v = 0 and v = 1 were selected to isolate only those dissociation channels including coincident ground state I(2P 3/2). Velocity-resolved alignment and orientation parameters are determined from the observed Doppler profiles. The alignment measurements for both v = 0 and v = 1 levels are very similar, and consistent with dissociation occurring via three distinct pathways, beginning with simultaneous excitation of the 4A'(3Π0+), 5A'(1Π1) and 5A″(1Π1) surfaces. While the incoherent alignment parameters for both v = 0 and v = 1 products are similar, the corresponding coherent orientation parameters are markedly different. CN (v = 0, N) exhibits a large positive orientation, whereas all rotational states probed in v = 1 show a much smaller orientation. This is consistent with the previously observed change in the sign of the coherent orientation parameter between v = 0 and v = 2. © 2010 Taylor and Francis.